Management of stroke in emergency department in relation to blood pressure, blood sugar and use of anti-thrombotic agents - Aryal, M; Niraula, S; Shahukhal, R; Mainali, NR; Sigdel, S; Giri, S; Pandey, S; Shakya, YL (Journal of Institute of Medicine Nepal, 2010)
Introduction: Since the Emergency Department (ED) of TUTH lacks uniformity in the treatment of stroke patients, it is assumed that these patients do not receive standard treatment in terms of reduction of blood pressure (BP), control of hyperglycemia and treatment with antithrombotic agents. Our hospital-based study aims to assess the mean stay of stroke patients in the ED and the level of optimal treatment they are getting. Methods: A retrospective hospital-based study among 82 patients diagnosed as CVA in the ED (who later got admitted), was carried out using medical records. History, clinical examinations, investigations and treatment given were analysed to gather relevant information. Results: Mean age of occurrence of stroke in the inpatients visiting ED was found to be 62.4 years. Average duration of stay in the ED before admission was 13 hours. Ischaemic stroke was almost four times more common than haemorrhagic stoke. All the patients with haemorrhagic stroke who had indication for reduction in BP received antihypertensive medications. However, 28% of the patients with ischaemic stroke, eventhough having indication for BP reduction, did not receive antihypertensives. Out of 11 patients who had an indication for reduction in blood sugar, only one patient (9%) received treatment with insulin. Only 52% of the patients who had ischaemic stroke received treatment with aspirin. Conclusions: There is lack of uniformity regarding the treatment of stroke in terms of blood pressure reduction, hyperglycemia and antithrombotic treatment. A standard protocol needs to be developed in order to bring uniformity and efficiency in the treatment of stroke. DOI: http://dx.doi.org/10.3126/joim.v32i1.3995 Journal of Institute of Medicine, April, 2010; 32:1 pp.11-14